Csend és kiáltás – aka Silence et cri . Silence and Cry - Jancsó, Miklós (MAFILM, 1968)
Duration: 01:23:00 The friendship between two childhood friends is tested in this political drama. After an abortive attempt by the Communists to seize power in 1919 Hungary, the authorities set out to find the insurgents. István Cserzi, a former soldier of the Red Army has fled to the Great Hungarian Plains and has taken refuge on a farm, which is run by two sympathetic women. Due to the generosity of these women and a former childhood pal, who is now a commandant of the local Royal Gendarme outfit, István is safely hidden from the ever-prying eyes of the secret policemen, who relentlessly roam the countryside searching for ex-Red Army men and their sympathisers. However, upon discovering that the women are secretly poisoning the mother-in-law and the husband, the legal owners of the farm, István must make the most difficult decision of his life. As a personal war is waging within his own consciousness over morality and self-preservation, István must decide whether to remain silent about the women's devious secret and preserve his own life, or to report their heinous crime to the Royal Gendarme, which would also mean certain death for him.